Title: A Systematic Review of Open-Source GIS Platforms: Capabilities, Limitations, and Adoption - Partab Rathore; Muhammad Junaid Ahmad; Muhammad Zain; Ayesha Shafiq; Muhammad Junaid Bin Zulfiqar (International Journal of Education, Vocational and Social Science, 2025)
The integration of Geographic Information Systems (GIS) with remote sensing and artificial intelligence (AI) is transforming the landscape of spatial analysis. This review explores the evolution, capabilities, and adoption of prominent open source GIS platforms including QGIS, GRASS GIS, gvSIG, SAGA GIS, ILWIS, and Whitebox GAT. These tools have emerged as robust alternatives to proprietary software, offering flexibility, extensibility, and community-driven innovation. The paper examines their origins, key features, licensing models, and comparative strengths in handling raster-vector analysis, plugin support, and web-based mapping. It further highlights adoption trends in academia, government, and non-profit sectors, along with educational integration and migration patterns from commercial platforms. Current limitations such as steep learning curves and performance with large datasets are addressed. The review concludes by outlining future directions, including AI integration, real time analytics, cloud deployment, and enhanced interoperability. By synthesizing literature and case examples, this paper underscores how open-source GIS, in combination with remote sensing and AI, is shaping a new era in spatial intelligence.